2018
DOI: 10.1097/moo.0000000000000436
|View full text |Cite
|
Sign up to set email alerts
|

Salivary duct carcinoma

Abstract: The aggressive SDC is increasingly diagnosed. Despite intensive combined surgery and radiation therapy, many patients recur, for whom new bullets, targeting the molecular biological mechanisms, are the subject of ongoing clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 51 publications
1
46
0
Order By: Relevance
“…The lack of p63 staining will also distinguish SDC from metastatic squamous‐cell carcinoma. Up to a half of SDCs will demonstrate ERBB2 amplification by FISH or overexpression of HER2 by IHC . If present, PLAG1 and HMGA2 rearrangements suggest that an SDC arose as a carcinoma ex PA, though the lack of these cytogenetic alterations does not exclude this possibility.…”
Section: Malignant Neoplasmsmentioning
confidence: 98%
See 1 more Smart Citation
“…The lack of p63 staining will also distinguish SDC from metastatic squamous‐cell carcinoma. Up to a half of SDCs will demonstrate ERBB2 amplification by FISH or overexpression of HER2 by IHC . If present, PLAG1 and HMGA2 rearrangements suggest that an SDC arose as a carcinoma ex PA, though the lack of these cytogenetic alterations does not exclude this possibility.…”
Section: Malignant Neoplasmsmentioning
confidence: 98%
“…Cytology smears reveal clusters of round to oval cells with fine to slightly granular chromatin and granular to dense cytoplasm with occasional intracytoplasmic vacuoles forming sheets, cribriform structures, or tubules. Nuclei are often pleomorphic with prominent nucleoli . Occasional binucleate or multinucleated cells are common (Figure ).…”
Section: Malignant Neoplasmsmentioning
confidence: 99%
“…19 In a manner similar to ACC, PNI is a common feature of SDC, which is identified in 69% of cases and has been reported to be a negative prognostic factor for this high-grade aggressive tumor. 69 Other high-grade salivary gland histologies, such as high-grade mucoepidermoid carcinoma, are also associated with PNI. 70 The superficial and deep lobes of the parotid are separated by the facial nerve (VII), which gives rise to the 5 terminal branches within the gland that then innervate the muscles of facial expression.…”
Section: Parotid Glandmentioning
confidence: 99%
“…Salivary duct carcinoma (SDC) is an uncommon and aggressive tumour that accounts for approximately 10% of all salivary gland malignancies . It occurs not only as de‐novo carcinoma, but also as malignant transformation from pleomorphic adenoma.…”
Section: Introductionmentioning
confidence: 99%
“…A multivariate analysis revealed that SDCs with Introduction Salivary duct carcinoma (SDC) is an uncommon and aggressive tumour that accounts for approximately 10% of all salivary gland malignancies. [1][2][3] It occurs not only as de-novo carcinoma, but also as malignant transformation from pleomorphic adenoma. SDC is histologically comparable to high-grade mammary ductal carcinoma.…”
mentioning
confidence: 99%